2022
DOI: 10.1089/tmj.2021.0041
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Telemedicine's “New Normal”: Variations in Telemedicine Use by Specialty Line and Patient Demographics

Abstract: Background: Our objective was to examine the variation in telemedicine adoption by specialty line and patient demographic characteristics after the initial peak period of the coronavirus disease 2019 pandemic when in-person visits had resumed and visit volume returned to prepandemic levels. Materials and Methods: Aggregated encounter data were extracted for six service lines (dermatology, psychiatry, endocrinology, cardiology, orthopedics, and nonurgent primary care) in an integrated health system across three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
96
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 40 publications
7
96
1
Order By: Relevance
“…In contrast, Drake et al's study reported black patients 10% less likely than those of white race to use telemedicine (OR = 0.90, 95% CI: 0.88-0.91). [16] Kakani et al's study showed no significant difference in telemedicine use between black and white patients (OR = 0.98, 95% CI: 0.92-1.04). [15] Although the Drake and Kakani studies used academic health center encounter data, the studies were conducted in geographically different regions of the country, North Carolina and California, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, Drake et al's study reported black patients 10% less likely than those of white race to use telemedicine (OR = 0.90, 95% CI: 0.88-0.91). [16] Kakani et al's study showed no significant difference in telemedicine use between black and white patients (OR = 0.98, 95% CI: 0.92-1.04). [15] Although the Drake and Kakani studies used academic health center encounter data, the studies were conducted in geographically different regions of the country, North Carolina and California, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, our primary outcome was focused on forward triage, the ability to minimize in-person encounters. 20 Future studies with comparator groups are required to investigate the effectiveness of telemedicine for key metrics such as patient outcomes, cost-effectiveness, and sustainability. 11 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our findings highlight demographic and clinical differences in health care use for SARS-CoV-2 testing across all care delivery settings, which can strategically inform outreach efforts for distinct populations. Without structural reforms, rapid implementation of telehealth and other new services may exacerbate inequities in access to care, 2 , 3 , 4 , 5 particularly if these investments come at the expense of other care sites.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic rapidly shifted care delivery toward telehealth and COVID-19 testing services. While utilization differences early in the pandemic have been described among commercially insured patients and in ambulatory care settings, 1 , 2 , 3 health care use patterns for SARS-CoV-2 testing and subsequent health care use remain unclear, especially among safety-net populations.…”
Section: Introductionmentioning
confidence: 99%